Ręczna broń palna w świetle rejestrów popisowych piechoty zaciężnej z lat 1471–1500 - Grabarczyk, Tadeusz (Acta Universitatis Lodziensis. Folia Historica, 1999)
First mentions concerning handfirearms in Poland are dated from 1410. The oldest type of such weapon, found in Lwow, is dated from the first half of the XVth century. Mercenary infantry played an important part in popularization of handfirearms. Armament of mercenary infantry is known thanks to registers of the troops (from 1471, 1477, 1496, 1498, 1497, 1500) which are preserved. Comparing to other armies, schooters played an important part in Polish infantry. On the average 75% of all infantrymen were schooters. In 1471 and in 1477 infantry schooters were armed with swords and first of all with crossbows. Only 16 among 2000 schooters had firearms that time. The registers from 1496-1500 show growing popularity of handfirearms among mercenary infantry troops. In 1496 27,1% of schooters were armed with firearms, in 1497 – 54%, in 1498 – 60%, in 1500 – almost 63%. Thanks to the registers a process of rapid weapon exchange can be observed. Descriptions of battles from the early XVIth century show us that using of firearms had a serous influence on struggle’s final result. It happened so for example during battles of Kiecko (1506), Orsza (1514) and Obertyn (1531), where infantry was armed like the troops mentioned in the registers. Basing on the registers, we can say that professional mercenary soldiers prefered handfirearms to crossbows, considering them to be more efficient.